PENGARUH INDEKS INFRASTRUKTUR JALAN TERHADAP INDIKATOR EKONOMI DI INDONESIA - Prayoga Luthfil Hadi; Tilaka Wasanta; Wimpy Santosa (Himpunan Pengembangan Jalan Indonesia (HPJI), 2021)
Abstract Roads and bridges are the main infrastructure in supporting the realization of increased economic development. The relationship between the performance of road infrastructure provision and the improvement of economic performance is a very important aspect to understand. The magnitude of this relationship can be used as the basis for making decisions on road infrastructure development. The road infrastructure index is a parameter that can be used to measure road infrastructure services to the economy. The road infrastructure index used in this study is a comparison of road length with area and population. This infrastructure index is then analyzed in relation to economic indicators, such as Gross Regional Domestic Product and poverty index. This study shows that an increase in the area index helps improve socioeconomic indicators, such as an increase in GRDP and a decrease in the poverty index. Meanwhile, the increase in the value of the population index has a negative relationship with the growth of socioeconomic indicators, which means that the larger the population index, the worse the socioeconomic indicators. An increase in the population infrastructure index causes a decrease in the GRDP indicator and an increase in the poverty index, which means that longer roads are needed to serve the population. Keywords: road; infrastructure performance; road infrastructure index; economic indicators. Abstrak Jalan dan jembatan merupakan suatu infrastruktur utama dalam mendukung terwujudnya peningkatan pembangunan ekonomi. Hubungan antara kinerja penyediaan infrastruktur jalan dengan peningkatan kinerja ekonomi merupakan aspek yang sangat penting untuk dimengerti. Besaran hubungan ini dapat dijadikan dasar untuk pengambilan keputusan pembangunan infrastruktur jalan. Indeks infrastruktur jalan merupakan parameter yang dapat digunakan untuk mengukur layanan infrastruktur jalan terhadap ekonomi. Indeks infrastruktur jalan yang digunakan pada studi ini adalah perbandingan panjang jalan dengan luas wilayah dan jumlah penduduk. Indeks infrastruktur ini kemudian dianalisis keterkaitannya dengan indikator ekonomi, seperti Produk Domestik Regional Bruto dan indeks kemiskinan. Studi ini menunjukkan bahwa kenaikan indeks luas wilayah membantu perbaikan indikator sosioekonomi, seperti kenaikan PDRB dan penurunan indeks kemiskinan. Sedangkan kenaikan nilai indeks penduduk memiliki hubungan negatif dengan pertumbuhan indikator sosioekonomi, yang berarti semakin besar indeks penduduk, indikator sosioekonomi memburuk. Kenaikan indeks infrastruktur penduduk menyebabkan penurunan pada indikator PDRB dan kenaikan pada indeks kemiskinan, yang berarti diperlukan jalan yang lebih panjang untuk melayani penduduk. Kata-kata kunci: jalan; kinerja infrastruktur; indeks infrastruktur jalan; indikator ekonomi.